Effective and efficient attendance tracking system using secret code - Zhi T.J.; Ibrahim Z.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Codes (symbols); Cryptography; Education; Tracking (position); Hashing algorithms; MD5 Hashing; NFC; Secret code; Tracking system; Students